2007
DOI: 10.1021/jp074025x
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Different Isomers of the Photochromic CMTE Molecule on the Si(100) Surface Studied by STM

Abstract: The adsorption of the cis-1,2-dicyano-1,2-bis(2,4,5-trimethyl-3-thienyl)ethene (CMTE) molecule on the clean Si(100)-2 × 1 surface was studied using scanning tunneling microscopy at room temperature. These molecules belong to the class of photochromic dye molecules that undergo reversible photoisomerization between the open and closed isomers when irradiated with light. This is the first observation of individual photochromic molecules on a surface where it is possible to identify the two photoisomers. By chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The continuation of work on large molecules, such as 1,4 -paratriphenyldimethylacetone molecule (trima) [478] as well as an investigation of cis-1,2-dicyano-1,2-bis(2,4,5-trimethyl-3-thienyl)ethene (CMTE), a photochromic dye, on Si(100)-2×1 [479] is also now available.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…The continuation of work on large molecules, such as 1,4 -paratriphenyldimethylacetone molecule (trima) [478] as well as an investigation of cis-1,2-dicyano-1,2-bis(2,4,5-trimethyl-3-thienyl)ethene (CMTE), a photochromic dye, on Si(100)-2×1 [479] is also now available.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…A possible scenario in which the adsorption configuration is heavily influenced by the surface through the formation of a SiÀ S bond that forces the two thiophene rings in different configurations has been proposed. [79] Meanwhile, in a separate study, Coudret and co-workers observed standing waves when a diarylethene derivative was adsorbed on Cu (111) surface. [80] This pointed to interactions with the Cu surface.…”
Section: Diarylethenes Under Uhvmentioning
confidence: 98%
“…With the aid of calculations, these were assigned to their o and c forms. A possible scenario in which the adsorption configuration is heavily influenced by the surface through the formation of a Si−S bond that forces the two thiophene rings in different configurations has been proposed …”
Section: Stm Of Diarylethenesmentioning
confidence: 99%
“…Understanding and controlling conformational changes of molecules adsorbed on surfaces is one of the most actively pursued goals related to fundamental electronic device miniaturization . So far, many isomerization reactions have been studied for molecules adsorbed on surfaces , by activating the reactions via photon excitation, by means of tunnel electrons, or with the electrostatic field under the tip of STM. …”
Section: Introductionmentioning
confidence: 99%